PUBLICATIONS OF THE WEEK. (Bookseller, 2003)
Publications of the Week is a service offered by 'The Bookseller' consisting of newly-published titles. The list is prepared by Nielsen BookData and contains titles published this year filed by classification and alphabetically under author. More comprehensive bibliographic information including over 1,300,000 in-print titles and the names and addresses of over 50,000 active publishers is available on CD-ROM, DVD, microfiche and online. The list includes books on agriculture, air transport, biology, careers, chemistry and computers among others.